JURISDICTIONAL STATUS OF THE POLISH RECHTSPFLEGER - Małgorzata, Arkuszewska Aneta; Anna, Kościółek (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The purpose of the paper is to introduce the office of the Rechtspfleger in Poland. The office of the Rechtspfleger is a relatively new institution in the Polish judiciary, whilst in other European countries it has a longer tradition. It was first established in Austria and Germany, and subsequently in: Belgium, Denmark, Finland, France, Hungary, Italy, Luxembourg, the Netherlands, Portugal, Spain, Sweden. The office is also known in such non-European countries as Morocco, Tunisia or even Japan. There is no complex normative regulation concerning the office of the Rechtspfleger. Regulations regarding the Rechtspfleger's occupational status are included in the Common Courts Organization Act, whilst the Rechtspfleger's powers are defined mostly in the Code of Civil Procedure and in some other acts such as: the Civil Court Fees Act, the Land and Mortgage Registers and Mortgage Act and others. The paper mainly concerns the jurisdictional status of the office. In consequence, the following remarks deal with the Rechtspfleger's powers in litigious proceedings, non-litigious proceedings (including land and mortgage proceedings, register proceedings, inheritance proceedings and compensatory proceedings), enforcement proceedings and international proceedings, as well as with means of appeal against the Rechtspfleger's judgments (the complaint on actions of the Rechtspfleger). Keywords : office of the Rechtspfleger, Polish judiciary, normative regulation, Code of Civil Procedure, the jurisdictional status.